Effect of a National Nutrition Communications Campaign on Stunting Awareness and Promotion of Exclusive Breastfeeding Behavior among Rural Indonesian Mothers - Moffat, Ryan Craig; Sayer, Alexis; Hawks, Megan; DeCook, Kiersten; Traub, McKayla; Linehan, Mary; Dearden, Kirk; Rachmi, Cut Novianti; West, Josh; Crookston, Benjamin; Hall, Cougar (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Stunting affects 37% of Indonesian children and has lifelong consequences for the affected child. Childhood stunting can be prevented by promoting exclusive breastfeeding (EBF) and helping mothers overcome barriers to EBF. This study aimed to examine the effect of a National Nutrition Communications Campaign (NNCC) on stunting awareness and promotion of exclusive breastfeeding behavior among rural Indonesian mothers. Subjects and Method: Data came from interviews and a cross-sectional survey of 1,740 mothers with children under the age of 2 in three Indonesian districts, from November 2015 to March 2018. Measures included exposure to two different NNCC interventions: multi-media messages (media) and interpersonal communication strategies (IPC) and associations with stunting knowledge, breastfeeding knowledge, and breastfeeding perceptions/intentions. The data were analyzed by a multiple logistic regression. Results: Exposure to NNCC was positively associated with knowledge toward EBF (OR= 1.56; 95% CI= 1.10 to 2.19; p= 0.043), awareness of the importance of nutrition during the first 1000 days of life (OR= 1.90; 95% CI= 1.43 to 2.52; p<0.001), and having heard of stunting (OR= 1.93; 95% CI= 1.41 to 2.63; p<0.001). Exposure to IPC was positively associated with knowledge toward EBF (OR=1.78, CI95% 1.37 to 2.30, p<0.001), awareness of the importance of nutrition during the first 1000 days of life (OR= 3.02; 95% CI= 2.40 to 3.80; p<0.001), knowledge of EBF benefit to prevent stunting (OR= 3.05; CI 95%= 2.33 to 3.98; p<0.001), and having heard of stunting (OR= 3.15; CI 95%= 2.49 to 3.98; p<0.001). Exposure to IPC was a significant predictor of an intention to engage in EBF (p <0.050). Conclusion: These findings point to practical recommendations for national level social and behavior change communication efforts. Future campaigns should aim to be inclusive of: 1) mass media (television, radio, billboards, and social media) to promote health as these efforts provide for wide exposure while maintaining impact; and 2) IPC (face-to-face communications, classes, and support groups) as these efforts increase knowledge and impact on behavior, beliefs and intentions.